The Effect Of Hydration Education Using Animated Videos On Changes In Water Consumption Habits Among Elementary School Students - Ario Aditya Eka Saputra; Roby Aji Permana (Journal of Nursing Periodic, 2026)
Introduction: Hydration is an important physiological need in maintaining body balance and cognitive function in school-age children. Inadequate fluid intake may increase the risk of mild dehydration which affects concentration and learning readiness. Hydration education using animated video is considered effective because it combines visual and audio elements that attract children’s attention. This study aimed to analyze the effect of hydration education using animated video on changes in drinking water behavior among elementary school students. Methods: This study used a quantitative pre-experimental design with a one-group pretest-posttest approach. The study population consisted of fifth and sixth-grade students, with 60 respondents selected using proportional random sampling techniques. The independent variable was hydration education using animated video media, while the dependent variable was drinking water habit behavior. Data were collected using the Fluid Intake and Hydration Questionnaire (FIHQ). Statistical analysis was performed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The study applied ethical principles including informed consent, anonymity, beneficence, non-maleficence, and justice. Results: The results showed that before intervention, most respondents had moderate drinking water behavior. After hydration education using animated video, respondents with good drinking water behavior increased. Statistical analysis showed p-value = 0.000 (p < 0.05), indicating a significant effect of hydration education using animated video on changes in drinking water behavior among elementary school students. Conclusions: Hydration education using animated video significantly improved drinking water habits among elementary school students. Animated educational media can be used as an innovative health promotion strategy to encourage healthy hydration behavior in school-age children